Kajian Literatur Efektivitas Program Makanan Bergizi Gratis Terhadap Perbaikan Status Gizi Anak Sekolah - Miftahurrahmah El Hayatli; Izmi Raditya Putri; Tiara Putri Azzahra Tamin; Abellia Putri; Sekar Giovany Afif Nababan (CV. ITTC INDONESIA, 2026)
Nutritional problems among school-aged children remain a public health challenge in Indonesia as they can affect physical growth, cognitive development, and academic performance. One of the government's efforts to address this issue is the Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG). This study aims to analyze the effectiveness of the Free Nutritious Meal Program in improving the nutritional status of school-aged children based on published research findings. The study employed a descriptive literature review approach. Data were collected from national and international scientific articles published between 2021 and 2026 through Google Scholar and PubMed databases. Articles were selected based on predetermined inclusion and exclusion criteria and analyzed qualitatively through research synthesis. The findings indicate that the Free Nutritious Meal Program has a positive impact on improving children's nutritional status by increasing the intake of energy, protein, vitamins, and minerals. The program also contributes to improved school attendance, learning concentration, and educational outcomes. Furthermore, MBG has the potential to serve as a long-term investment in developing healthy and productive human resources. However, the effectiveness of the program is influenced by several factors, including menu quality, food distribution, food safety, funding availability, and monitoring and evaluation systems. Therefore, the Free Nutritious Meal Program can be considered an effective strategy for improving the nutritional status of school-aged children when supported by proper and sustainable program management.